2014
DOI: 10.1523/jneurosci.0128-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Unlearning: NMDA Receptor-Mediated Metaplasticity in the Anterior Piriform Cortex Following Early Odor Preference Training in Rats

Abstract: Here we demonstrate metaplastic effect of a change in NMDA receptor (NMDAR) number in the anterior piriform cortex (aPC) in rat induced by a 10 min pairing of peppermint odor ϩ stroking, which significantly modifies later learning and memory. Using isolated synaptoneurosomes, we found NR1 receptor downregulation 3 h after training and upregulation at 24 h. Consistent with the NR1 pattern, the NMDAR-mediated EPSP was smaller at 3 h and larger at 24 h. Subunit composition was unchanged. Whereas LTP was reduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…This led us to the idea that the regulation of the receptor was not at the protein expression level as seen in other memory models (Baez et al 2013) but rather at the surface expression level. The regulation at the surface expression level has been repeatedly reported in memory and synaptic plasticity experiments (Cammarota et al 2000;Grosshans et al 2002b;Moyano et al 2004;Mukherjee et al 2014).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This led us to the idea that the regulation of the receptor was not at the protein expression level as seen in other memory models (Baez et al 2013) but rather at the surface expression level. The regulation at the surface expression level has been repeatedly reported in memory and synaptic plasticity experiments (Cammarota et al 2000;Grosshans et al 2002b;Moyano et al 2004;Mukherjee et al 2014).…”
Section: Discussionmentioning
confidence: 78%
“…We thank Kevin Michael Boergens for language revision of the manuscript. This work was supported with grants from the University of Buenos Aires (UBACyT 2011-2014 20020100200268, UBACyT 2014-2017, from the CONICET (PIP 2011(PIP -2013 and from FonCyT (Grant PICT2010-0391, Grant PICT2013-1657, Grant PICT2013-0412).…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…In a step-down inhibitory avoidance of a mild foot-electric shock, Cammarota et al [ 46 ] showed that there was an increase of GluN1 in hippocampal synaptosomal fractions (by western blot), without significant changes in GluN2A or in GluN2B 30 minutes after training; 120 minutes after training, NMDAR subunits level was similar to controls. Mukherjee et al [ 47 , 48 ] showed that, in P7 to P10 pups, when the developmental switch from GluN2B to GluN2A did not take place yet [ 12 ], there was a change in NMDAR as the absolute amount of the essential GluN1 decreased three hours after one training session in an odor preference task. This decrease was observed in synaptosomal fractions of the anterior piriform cortex [ 47 ] and in postsynaptic density fractions [ 48 ].…”
Section: Nmdar Expression and Memory Acquisition ( Tablementioning
confidence: 99%
“…Mukherjee et al [ 47 , 48 ] showed that, in P7 to P10 pups, when the developmental switch from GluN2B to GluN2A did not take place yet [ 12 ], there was a change in NMDAR as the absolute amount of the essential GluN1 decreased three hours after one training session in an odor preference task. This decrease was observed in synaptosomal fractions of the anterior piriform cortex [ 47 ] and in postsynaptic density fractions [ 48 ]. However, 24 h after training, GluN1 level was not significantly different compared to controls, indicating that the modification was transient.…”
Section: Nmdar Expression and Memory Acquisition ( Tablementioning
confidence: 99%
“…Since then evidence has been obtained for a major role of NMDA receptors in synaptic transmission and plasticity including learning and memory and other aspects of cognition (Tsien et al ; Cammarota et al ; Bartlett et al ; Berberich et al ; Zorumski and Izumi ; Paoletti et al ; Mukherjee et al ). Since maintained or excessive activation of NMDA receptors causes cellular calcium overload, quinolinic acid can produce excitotoxicity and neurodegeneration (Stone and Addae ; Kalia et al ; Hardingham ; Hardingham and Bading ; Danysz and Parsons, ; Guillemin, ; Stone et al ,b; Lovelace et al ), again balanced or prevented by endogenous levels of kynurenic acid (Harris et al ; Sapko et al ; Stone and Darlington ).…”
Section: Introduction: the Kynurenine Pathway And Receptorsmentioning
confidence: 99%